2020
DOI: 10.1097/md.0000000000020946
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phenylephrine infusion on hypotension induced by the beach chair position

Abstract: Background: The beach chair position (BCP), used during shoulder surgery, is associated with hypotension, bradycardia, and risk of cerebral hypoperfusion. Phenylephrine is commonly used as a first treatment of choice of intraoperative hypotension during surgery. We evaluated the hemodynamic effects of 2 doses of intravenous phenylephrine infusion administered before being placed in BCP for arthroscopic shoulder surgery. The primary endpoint was the incidence of hypotension after positional change.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…After positioning we revealed further decreasing of SBP, DBP and MAP. Our data are similar to those obtained by M. Ko et al [14]. The total incidence of hypotension after placement into the BCP in their investigation came up 93.65 % in all patients.…”
Section: Parameterssupporting
confidence: 92%
“…After positioning we revealed further decreasing of SBP, DBP and MAP. Our data are similar to those obtained by M. Ko et al [14]. The total incidence of hypotension after placement into the BCP in their investigation came up 93.65 % in all patients.…”
Section: Parameterssupporting
confidence: 92%
“…However, one of the most common push dose pressors to treat hypotension in the critically ill, whether related to intubation or not (57.3% of patients utilized push dose pressors for ETI vs 38.2% of patients utilizing push dose pressors for transient hypotension according to 1 report 18 ), is phenylephrine. 1921 Unlike norepinephrine which stimulates α 1 /α 2 receptors in addition to slight activity at β 1 /β 2 receptors, phenylephrine is a pure α 1 receptor agonist causing constriction of larger arterioles rather than terminal arterioles. 22 A prior randomized controlled trial concluded that there was no difference in outcomes when phenylephrine, instead of norepinephrine, was used as the first-line vasopressor for patients in septic shock.…”
Section: Discussionmentioning
confidence: 99%